Pemetaan Potensi Lahan di Kabupaten Tapin Kalimantan Selatan Menggunakan Sistem Informasi Geografis (SIG) - Nurrahmah, Daratun; Nurlina, Nurlina; Siregar, Simon Sadok (Lambung Mangkurat University Press, 2010)
In this research, SIG is used to analyse potency of land in KabupatenTapin, using method of scoring of parameters such us of ground type, rock type,bevel inclination, irrigate surface, and erotion level. Every parameter classified byaccording to reference, later then analysed with method overlay, and conductedby a calculation make an index to land potency. Map of potency of land yieldedfrom method of scoring of parameter consisted of 5 classes that is very high,high, medium, low, and very low. As according to function from area of divisibleland become 5 areas, among other things the covert area, prop area, limitedpreserve area, preserve area of annual crop and area of season crop. Spasialmodeled make an index to land potency give good result, because having asaccording to plan of regional planology that existed in Kabupaten TapinKalimantan Selatan.